PROSES PENYELESAIAN SENGKETA TANAH SECARA ADAT DI DESA CUNCA LOLOS KECAMATAN MBELILING KABUPATEN MANGGARAI BARAT - Sari, Lilis Anjas; Masu, Reny Rebeka; Resopijani, A (Petitum Law Journal, 2024)
Customary law was born at the same time as humans as its creators. Where there is society there is law (Ibi Ius Ibi Societas). At the implementation level, customary law can provide decisions that prioritize the goal of achieving togetherness and upholding the principle of kinship, rather than upholding provisions that have been determined by the government with positive law which tends to ignore togetherness and the principle of kinship. Cunca Lolos Village is one of the traditional villages in West Manggarai, therefore every problem in Cunca Lulus Village is resolved through adata and the same applies to the application of cultural values ​​and traditions in Cunca Lolos Village, Mbeliling District, West Manggarai Regency in resolving property disputes. This research is empirical legal research. This research is descriptive in nature and analyzes primary data to determine the process of resolving customary land disputes in the village of Cunca Lolos. Data collection uses interview, observation and documentation techniques. The results of this research show that; (1) the customary land dispute resolution process in Cunca Lulu village is divided into two parts, namely the land settlement process based on stages and the land settlement process based on land ownership (2) the inhibiting factors include changing times which have resulted in the loss of respect for tua golo and how difficult it is to collect old golo devices when completing a task in the village of Cunca escaped.